Efektifitas Pendidikan Kesehatan Terhadap Perilaku Sleep Hygiene Dan Kualitas Tidur Pada Remaja Dengan Gangguan Tidur - Ni Luh Agustini Purnama; Veronica Silalahi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Sleep is one of the basic human needs that is important for physical growth and intellectual development of adolescents are prone to sleep disorders due to poor sleep hygiene behavior. The purpose of this study was to identify the effectiveness of health education with booklet and audiovisual media on sleep hygiene behavior and sleep quality in adolescents with sleep disorders. The research design used was Quasy Experimental. The research will be conducted at the Karitas Catholic High School 3 Surabaya. Sampling with a saturated sampling technique consisting of 89 adolescents with sleep disorders. The independent variable of this study was health education using audiovisual media and booklets, while the dependent variable was sleep hygiene behavior and sleep quality. Sleep hygiene behavior was assessed using the Adolescent Sleep Hygiene Scale (ASHS) questionnaire and sleep quality was measured using the PSQI (Pittsburgh Sleep Quality Index) instrument. Data analysis in this study used a univariate test on each variable and a bivariate test to determine differences in sleep hygiene behavior and sleep quality before and after the intervention and to test the effectiveness of audiovisuals and booklets on sleep hygiene behavior and adolescent sleep quality. The bivariate test used in this study was Wilcoxon and Mann Whitney. Data processing and analysis using statistical data processing computer programs with a significance level of p <0.05 and 95% confidence intervals. Health education using the booklet and audiovisual media effectively improves adolescent sleep hygiene behavior with sleep disorders (p = 0.001). Health education with booklet and audiovisual media effectively improves the sleep quality of adolescents with sleep disorders (p = 0.001). There is no significant difference in sleep hygiene behavior and adolescent sleep quality given health education with booklet and audiovisual media (p = 0.59 ; p = 0.93). Health education with booklet and audiovisual media effectively improves sleep hygiene behavior and sleep quality of adolescents with sleep disorders